Hidden conservation vulnerability within a cryptic species complex: taxonomic revision of the spotted skink (Oligosoma lineoocellatum; Reptilia: Scincidae) from New Zealand - Melzer, Sabine; Bell, Trent; Patterson, Geoff B. (Zootaxa, 2017)
The diverse skink fauna of New Zealand comprises 40 described species within the single genus Oligosoma Girard, 1857. Cryptic species are common among New Zealand skinks, leaving numerous species undescribed. We used molecular phylogeny together with morphological analyses to distinguish four species in the spotted skink, Oligosoma lineoocellatum (Duméril & Duméril 1851), species complex. These are O. lineoocellatum sensu stricto, which is confined to the centre of the South Island, O. prasinum sp. nov. from the Lake Tekapo region, O. elium sp. nov. from the northern half of the South Island, and O. kokowai sp. nov. from the northern South Island, Cook Strait, and the North Island. Despite significant genetic differences, the morphological similarity of these species made it challenging to resolve their taxonomic identity. Three of the four species previously recognised as a single, widespread taxon are now recognised as threatened with extinction by a combination of invasive predatory mammals and land use change.